PENGARUH SERVICE QUALITY DAN SERVICESCAPE TERHADAP KEPUASAN PENGGUNA BRT TRANS SEMARANG - Ningmas Pertiwi, Seli; Widowati, Nina (Journal of Public Policy and Management Review, 2025)
BRT Trans Semarang is a strategic effort of Semarang City Transportation Agency through BLU UPTD Trans Semarang in organizing public transportation in Semarang City. However, there are 642 user complaints who are dissatisfied with Trans Semarang BRT services. This study aims to analyze the effect of service quality (X1) and servicescape (X2) on user satisfaction (Y) of BRT Trans Semarang using SERVQUAL theory from Parasuraman, Zeithaml, and Berry (1988) and SERVICESCAPE theory from Bitner (1992). The type of research used is descriptive quantitative with 100 respondents from Trans Semarang BRT users. The results of the analysis show that service quality has a partial positive effect on user satisfaction of 0.069. Servicescape has a partially positive and significant effect on user satisfaction of 0.211. Simultaneously, service quality and servicescape affect user satisfaction by 0.564 or 56.4%, while the remaining 43.6% is influenced by other factors not examined. Suggestions given by researchers to BLU UPTD Trans Semarang to increase user satisfaction of Trans Semarang BRT are to increase the intensity of cleaning bus stops, review travel routes, tighten the standardization of driver certificates, and design inclusive bus stops.